Heterotopic Pregnancy Secondary to in vitro Fertilization-Embryo Transfer: Risk Factors and Pregnancy Outcomes - Zhu, Shaomi; Fan, Yiyue; Lan, Ling; Deng, Tianqing; Zhang, Qinxiu (Frontiers in Medicine, 2022)
Background: With the widespread application of assisted reproduction technology (ART) and increased pelvic inflammatory disease, the incidence of heterotopic pregnancy (HP) has risen. However, the risk factors and treatment of HP remain indefinite. Objectives: To explore risk factors affecting the incidence of HP secondary to in vitro fertilization-embryo transfer (IVF-ET) and pregnancy outcomes after surgical treatment of HP. Methods: 29 patients with HP and 116 with an intrauterine-only pregnancy (IUP) after IVF-ET during the same period were included retrospectively from January 2015 to September 2020. Results: Patients with HP had a higher proportion of previous ectopic pregnancies, multiple abortion history (≧2 times) and tubal indication for IVF than IUP. Besides, they had a greater possibility to end in spontaneous abortion (31.03% vs.13.79%，P=0.028) and preterm delivery (25.00% vs. 7.00%, P=0.035), less possibility to result in a live birth (58.62% vs. 78.45%, P=0.028). History of multiple abortions (≥2 times) (odds ratio (OR) 3.031, 95% confidence intervals (CI) 1.087-8.453; P=0.034), tubal infertility (OR 3.844, 95% CI 1.268-11.656; P=0.017), previous ectopic pregnancies (OR 2.303, 95% CI 0.625-8.490; P=0.021) and number of embryo transfer (OR 0.300, 95% CI 0.092-0.983; P=0.037) resulted in an elevated proportion of HP in IVF treatment. Shorter operative duration, smaller size of the ectopic mass and location in the ampulla of the fallopian tube were associated with higher chance of survival in the coexistent intrauterine pregnancy after surgical treatment. Conclusions: Previous history of ectopic pregnancy, multiple abortions, tubal infertility and multiple-embryo transfer may be considered as meaningful risk factors of subsequent HP following IVF-ET. In patients with HP treated by surgery, shorter operative duration, smaller size of the ectopic mass and location in the ampulla of the fallopian tube means better reproductive prognosis.